To take risk in education requires time for exploration - Spanbroek, Nancy; Ridgewell, Brenda (WelTech, Victoria Universtiy of Wellington and Massey University, 2007)
Student/teacher time relationships are minimised in universities due to a range of fiscal directives. However, when analysing the success of design teaching, the time required for critical analysis through making and drawing, which is recognized as a crucial aspect of the development of the design project, is limited to the student. There is insufficient time for students to explore design ideas due to the reduced teaching time, condensed semesters, and high expectation of output. The thinking time the unmarked component becomes evident at the final stage of the project. It takes time to analyse, research and question a design approach.This paper presents a case study of the initiatives of an Experimental Design Studio in the Department of Interior Architecture, //// University of Technology, //// Australia. The studio addresses the perceived problems in our education system through an experimental project to encourage enquiry, inspire originality and set new standards for industry, avoiding the risk of mediocrity, one line statements and eclectic solutions. The risk here is giving the students the time to explore in a supportive learning environment.